2008
DOI: 10.1158/1541-7786.mcr-07-0396
|View full text |Cite
|
Sign up to set email alerts
|

Cripto-1 Alters Keratinocyte Differentiation via Blockade of Transforming Growth Factor-β1 Signaling: Role in Skin Carcinogenesis

Abstract: Cripto-1 is an epidermal growth factor-Cripto/FRL1/ Cryptic family member that plays a role in early embryogenesis as a coreceptor for Nodal and is overexpressed in human tumors. Here we report that in the two-stage mouse skin carcinogenesis model, Cripto-1 is highly up-regulated in tumor promotertreated normal skin and in benign papillomas. Treatment of primary mouse keratinocytes with Cripto-1 stimulated proliferation and induced expression of keratin 8 but blocked induction of the normal epidermal different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 34 publications
2
19
0
Order By: Relevance
“…Consistent with this notion, Smad7 is poorly expressed in the developing epidermis and is induced in the p63-null epidermis. It has been previously reported that Smad7 induces expression of Cripto-1, and that both Smad7 and Cripto-1 induce Krt8 expression in mouse keratinocytes (21,37). Loss of p63 does not affect Cripto-1 expression, 7 suggesting that other molecules downstream of Smad7 are required for repressing non-epidermal genes.…”
Section: Discussionmentioning
confidence: 93%
“…Consistent with this notion, Smad7 is poorly expressed in the developing epidermis and is induced in the p63-null epidermis. It has been previously reported that Smad7 induces expression of Cripto-1, and that both Smad7 and Cripto-1 induce Krt8 expression in mouse keratinocytes (21,37). Loss of p63 does not affect Cripto-1 expression, 7 suggesting that other molecules downstream of Smad7 are required for repressing non-epidermal genes.…”
Section: Discussionmentioning
confidence: 93%
“…ST and DT primary keratinocytes were cultured as previously described (Shukla et al, 2008) and after 3 days were infected with the c2ras retrovirus as described by Bae et al (2009). To induce TGFb1 expression, keratinocytes were cultured with 1 mg ml À1 dox for 3 days and total RNA was isolated, or culture supernatant was collected and concentrated using the Amicon Ultra-4 centrifugal device (Millipore Corp., Billerica, MA).…”
Section: Cell Culturementioning
confidence: 99%
“…Blocking the type I kinases, ALK5 (activin receptor-like kinase 5) receptor function abrogates TGFb signaling and inhibits epithelial cell morphology but stimulates smooth muscle cell differentiation in epicardial cells (Compton et al, 2006). Blocking ALK5 also inhibits keratinocyte differentiation (Shukla et al, 2008) and epithelial-mesenchymal transformation (Tojo et al, 2005). Upon activation of the receptors, both Smad and non-Smad intracellular signaling can be engaged.…”
Section: Introductionmentioning
confidence: 99%